What was the impact of a participatory research project in Australian Indigenous primary healthcare services? Applying a comprehensive framework for assessing translational health research to Lessons for the Best. Issue 2 (23rd February 2021) - Ramanathan, Shanthi Ann; Larkins, Sarah; Carlisle, Karen; Turner, Nalita; Bailie, Ross Stewart; Thompson, Sandra; Bainbridge, Roxanne; Deeming, Simon; Searles, Andrew
Abstract : Objectives: To (1) apply the Framework to Assess the Impact from Translational health research (FAIT) to Lessons from the Best to Better the Rest (LFTB), (2) report on impacts from LFTB and (3) assess the feasibility and outcomes from a retrospective application of FAIT. Setting: Three Indigenous primary healthcare (PHC) centres in the Northern Territory, Australia; project coordinating centre distributed between Townsville, Darwin and Cairns and the broader LFTB learning community across Australia. Participants: LFTB research team and one representative from each PHC centre. Primary and secondary outcome measures: Impact reported as (1) quantitative metrics within domains of benefit using a modified Payback Framework, (2) a cost-consequence analysis given a return on investment was not appropriate and (3) a narrative incorporating qualitative evidence of impact. Data were gathered through in-depth stakeholder interviews and a review of project documentation, outputs and relevant websites. Results: LFTB contributed to knowledge advancement in Indigenous PHC service delivery; enhanced existing capacity of health centre staff, researchers and health service users; enhanced supportive networks for quality improvement; and used a strengths-based approach highly valued by health centres. LFTB also leveraged between A1.4 and A1.6 million for the subsequent Leveraging Effective Ambulatory Practice (LEAP) Project to apply LFTB learnings to resource development and creation of a learning community to empower striving PHC centres. Conclusion: Retrospective application of FAIT to LFTB, although not ideal, was feasible. Prospective application would have allowed Indigenous community perspectives to be included. Greater appreciation of the full benefit of LFTB including a measure of return on investment will be possible when LEAP is complete. Future assessments of impact need to account for the limitations of fully capturing impact when intermediate/final impacts have not yet been realised and captured.